Trace Amine-Associated Receptor 2 Is Expressed in the Limbic Brain Areas and Is Involved in Dopamine Regulation and Adult Neurogenesis - Efimova, Evgeniya V.; Kuvarzin, Saveliy R.; Mor, Mikael S.; Katolikova, Nataliia V.; Shemiakova, Taisiia S.; Razenkova, Valeria; Ptukha, Maria; Kozlova, Alena A.; Murtazina, Ramilya Z.; Smirnova, Daria; Veshchitskii, Aleksandr A.; Merkulyeva, Natalia S.; et al. (Frontiers in Behavioral Neuroscience, 2022)
Trace amines are structurally close to classical monoamine neurotransmitters and can play an important role in regulating brain functions. Trace amine-associated receptors(TAARs) are emerging as promising targets for treating neuropsychiatric disorders. It was believed that all TAARs, apart from TAAR1, function as exclusively olfactory receptors involved in sensing innate odors encoded by volatile amines; however, recently, brain expression and function of TAAR5 were demonstrated. In this study we assessed the behavior, brain neurochemistry, and electrophysiology changes in knock-out mice, lacking TAAR2 but expressing beta-Galactosidase mapping expression of TAAR2 receptors. As expected, we detected beta-Galactosidase staining in the glomerular layer of the olfactory bulb. However, we found also staining in the deeper layers of the olfactory bulb and several brain regions, including the hippocampus, cerebellum, cortex, raphe nuclei, hypothalamus, and habenula, indicating that TAAR2 receptors are not only expressed in the olfactory system but are also present in the limbic brain areas receiving olfactory input. In behavioral experiments, TAAR2 knock-out(TAAR2-KO) mice showed increased locomotor activity and less immobility in the forced swim test, with no changes in anxiety level. Furthermore, TAAR2-KO mice showed alterations in brain electrophysiological activity – decreased spectral power of the cortex and striatum in the 0,9-20 Hz range. TAAR2-KO mice also had elevated tissue dopamine levels in the striatum and an increased dopaminergic neurons number in the Substantia Nigra. In addition, an increased brain-derived neurotrophic factor(BDNF) mRNA level in the striatum and Monoamine Oxidase B(MAO-B) mRNA level in the striatum and midbrain was found in TAAR2-KO mice. Importantly, TAAR2-KO mice demonstrated an increased neuroblast-like and proliferating cell number in the subventricular and subgranular zone, indicating increased adult neurogenesis. These data indicate that in addition to its role in the innate olfaction of volatile amines, TAAR2 is expressed in limbic brain areas and regulates the brain dopamine system, neuronal electrophysiological activity, and adult neurogenesis. These findings further corroborated observations in TAAR1-KO and TAAR5-KO mice, indicating common for TAAR family pattern of expression in limbic brain areas and role in regulating monoamine levels and adult neurogenesis; however, with variable involvement of each subtype of TAAR receptors in these functions.